Effects of Near-Fault Ground Motions on Civil Infrastructure - Camillo Nuti; Bruno Briseghella; Davide Lavorato; Ertugrul Taciroglu; Alessandro Vittorio Bergami (Applied Sciences, 2023)
Near-fault earthquakes (NFEs), characterized by high peak ground velocity (PGV) and long period pulses, show different properties from far-field ones [...]